Awareness of Time and Experience of Conscious Mental Processes during Musical Activity - Bjerstedt, Sven ; 0000-0002-3426-3322 (KronoScope, 2025)
How may changes in musicians’ experience of time influence their impressions of hav- ing conscious intentions during musical activity? In this essay I will present and discuss an autoethnographic account of how an exceptionally heightened awareness of time during musical improvisation may be connected to a heightened awareness of one’s own mental activity, particularly of speedy internal deliberative processes.
Keywords: awareness of time; mindlessness; mindfulness; deliberative processes; improvisation; mental activity